2018
DOI: 10.3390/min8020047
|View full text |Cite
|
Sign up to set email alerts
|

Acid-Gangue Interactions in Heap Leach Operations: A Review of the Role of Mineralogy for Predicting Ore Behaviour

Abstract: Abstract:Heap leaching accounts for a fifth of global copper production, sourced primarily from porphyry ores, yet metal recoveries are often not optimal. Gangue, and its interaction with acid, plays an important role in such processes. Thus, a proper understanding of gangue minerals present in the ore, their textural relationships relative to particle size distribution, reactivity with acid under different conditions, and relationship to lithotypes and geological alteration in the orebody, is necessary to pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…It can be concluded that there was low acid consumption to dissolve the gangue phases in the sample. These results are in accordance with those obtained by Chetty [28], in which species such as quartz and muscovite were considered of low solubility in an acid media. For the tests at 25 • C, the presence of unreacted chalcopyrite was determined.…”
Section: Characterization Of Leaching Residuessupporting
confidence: 92%
See 1 more Smart Citation
“…It can be concluded that there was low acid consumption to dissolve the gangue phases in the sample. These results are in accordance with those obtained by Chetty [28], in which species such as quartz and muscovite were considered of low solubility in an acid media. For the tests at 25 • C, the presence of unreacted chalcopyrite was determined.…”
Section: Characterization Of Leaching Residuessupporting
confidence: 92%
“…According to By et al [27], species such as quartz and biotite are not reactive against the presence of sulphuric acid. Muscovite was also declared to be of low reactivity in acid media [28]. Furthermore, pyrite is an inert sulphide, strong oxidants have to be employed for its efficient dissolution, and no such conditions exist in the proposed treatment [29].…”
Section: Initial Sample Characterizationmentioning
confidence: 99%
“…The slight increase in pH during leaching is due to the dolomite present as well as biotite, which, according to studies, is one of the most acid-reactive silicates [ 67 , 68 ], while to a lesser extent muscovite and albite [ 69 ]. Although the latter is less soluble in acid, grain size plays an important role in reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Silicates are the most common minerals in Earth's crust and mantle, making up 95% of the crust and 97% of the mantle by most estimates. Thus, it is necessary to understand their reactivity under the sulfuric acid regimes used in heap leaching to predict the behavior of the mineral and its impact on operations [60].…”
Section: Effect Of Clay Minerals On Copper Heap Leachingmentioning
confidence: 99%